COORDINATES OF THE POSTMODERN DIDACTICS IN THE EASTERN SPACE - Aura HAPENCIUC (Association of Social and Educational Innovation, 2020)
The paper analyzes the evolution of the instruction theory in Russia in the postmodern (contemporary) period, a historical context during which the curriculum paradigm is affirmed. Amongst the pedagogues with contributions at the level of general didactics, we chose the studies of four representative authors: I.K. Babansky, I.Ia.Lerner, V.V.Kraevsky, and M.N.Skatkin. In the analysis of their books, we followed the same coordinates: the axiomatic foundations / basic concepts that define the epistemological status of the general theory of instruction (which supports the foundations of pedagogy), their specific object of study, their specific normativity and their specific research methodology. The Russian pedagogy is concerned with the epistemic specificity of pedagogy as a specialized science in the study of education, and these concepts, which are found in general theories of the field, the general theory of education, the theory and methodology of instruction, the theory and methodology of the curriculum demonstrate its scientificity. The epistemological perspective of I.K. Babansky allows for the highlighting of the object of study and the specific norm. The object of study focuses on the interdependence between the actions of teaching, learning and evaluation. The curricular vision on the structure of the educational process concerns the relations between the component elements, both at the level of didactic actions and of the main links of the educational process (objectives, content, instruction methodology, didactic teacher - pupil interaction, evaluation). The normativity ensures the ordering of instruction by laws and principles of education. The epistemological foundations of didactics are fixed by I.Ia. Lerner at the level of links between goals - types of contents - methodology - teaching - learning and assessment methods, perfectible by involving the teacher's creativity (especially in the area of methods). The taxonomy of the methods, proposed by the pedagogue, combines the general purpose with the resource underlying the action of the method. The efficiency of the method depends upon the ability to achieve the optimal interdependence between the creativity of the teacher and the pupil, through self-learning methods in the classroom. The didactics of M.I. Skatkin proposes a global approach, building an ideal model of a concentric curricular circuit, starting from the social practice and its needs to the new level of instruction. M.I. Skatkin analyzes, from the perspective of historical pedagogy, the specific object of study of didactics (studied through fundamental concepts) and the normativity of the didactics (studied through the principles and laws of the educational process, the laws of instruction). V.V. Kraevsky proposes to overcome the problems of pedagogy through a research methodology that takes into account the unity between the theory and practice of education, such a methodology can ensure the unity of pedagogy. The table at the end is a synthesis of the paper, demonstrating the epistemological maturity of the analyzed texts, epistemically essentialized by the capitalizing on the fundamental concepts.